Adopting standardized cancer patient pathways as a policy at different organizational levels in the Swedish Health System - Petter Fjällström; Anna-Britt Coe; Mikael Lilja; Senada Hajdarevic (BMC, 2023)
Abstract Background Standardized cancer patient pathways as a new policy has been adopted in healthcare to improve the quality of cancer care. Within the health systems, actors at different levels manage the adoption of new policies to develop healthcare. The various actors on different levels play an important role and influence the policy adoption process. Thus, knowledge about how these actors use strategies when adopting cancer patient pathways as a policy in the health system becomes central. Method The study's aim was to explore how actors at different organizational levels in the health system adopted cancer patient pathways. Our overarching case was the Swedish health system at the national, regional, and local levels. Constructivist Grounded Theory Method was used to collect and analyze qualitative interviews with persons working in organizations directly involved in adopting cancer patient pathways at each level. Twelve individual and nine group interviews were conducted including 53 participants. Results Organizational actors at three different levels used distinct strategies during the adoption of cancer patient pathways: acting as-missionaries, fixers, and doers. Acting as missionaries consisted of preaching the idea of cancer patient pathways and framing it with a common purpose to agree upon. Acting as fixers entailed creating a space to put cancer patient pathways into practice and overcome challenges to this. Acting as doers comprised balancing breadth and speed in healthcare provision with not being involved in the development of cancer patient pathways for the local context. These strategies were not developed in isolation from the other organizational levels but rather, each level interacted with one another. Conclusions When adopting new policies, it is important to be aware of the different strategies and actors at various organizational levels in health systems. Even when actors on different levels developed separate strategies, if these contribute to fulfilling the four domains of inter-organizational collaboration, they can work well together to adopt new policies. Our study highlighted that the application of two domains was lacking, which meant that local actors were not sufficiently involved in collaboration, thus constricting the local use and optimization of cancer patient pathways in practice.